Scarcity effects of QE: A transaction-level analysis in the Bund market - Kathi Schlepper; Ryan Riordan; Heiko Hofer; Andreas Schrimpf (Deutsche Bundesbank, 2017)
This paper investigates the scarcity effects of quantitative easing (QE) policies, drawing on intra-day transaction-level data for German government bonds, purchased under the Public Sector Purchase Program (PSPP) of the ECB/Eurosystem. This paper is the first to match high-frequency QE purchase data with high-frequency inter-dealer data. We find economically significant price impacts at high (minute-by-minute) and low (daily) frequencies, highlighting the relevance of scarcity effects in bond markets. Asset purchase policies are not without side effects, though, as the induced scarcity has an adverse impact on liquidity conditions as measured by bid-ask spreads and inter-dealer order book depth. We further show that the price impact varies greatly with market conditions: it is considerably higher during episodes of illiquidity and when yields are higher.
Keywords: E52; E63; G11; G12; H63; 330; Quantitative Easing; European Central Bank; Scarcity Channel; Bond Market Liquidity; High-Frequency Data